Marine-derived L-asparaginase: unlocking marine power in anti-tumor therapeutics - Gopalakrishnan, Ritika; Kannan, Kamala; Gunasekaran, Ragul; Ramachandran, Priya; Ganapathy, Dhanraj; Sivaperumal, Pitchiah (Frontiers in Immunology, 2025)
L-asparaginase, a critical enzyme for cancer therapy, has been primarily produced by microbes. Researches are being conducted to identify better stabilizing, low immunogenicity and highly active alternative sources has focused on marine microorganisms. Marine-derived L-asparaginase is a promising candidate due to its unique characteristics and broad application potential. This review discusses the molecular structure, production-related genes, and the search for marine microbial sources of L-asparaginase production. Roles of L-asparaginase in cancer metabolism including asparagine depletion, apoptosis induction, autophagy and immunity are also detailed. Clinical studies with L-asparaginase in the treatment of pediatric and adult acute lymphoblastic leukemia is described, with indications for solid tumors. Also, combination therapy using L-asparaginase such as chemotherapy, targeted therapy, and immunotherapy has been explored to enhance therapeutic effects. The discovery of marine-derived L-asparaginase variants with improved properties holds great potential for expanding the utility of this enzyme across multiple sectors, unlocking the marine power in cancer prevention.